2009
DOI: 10.1001/archdermatol.2009.269
|View full text |Cite
|
Sign up to set email alerts
|

Text-Message Reminders to Improve Sunscreen Use

Abstract: To evaluate the effectiveness of cellular telephone text messaging as a reminder tool for improving adherence to sunscreen application.Design: We conducted a randomized, controlled trial of the effect of an electronic text-message reminder system on adherence to sunscreen application. Adherence to daily sunscreen use was evaluated using a novel electronic monitoring device.Setting: Participants were recruited from the general community.Participants: Seventy participants constituted a volunteer sample from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(102 citation statements)
references
References 34 publications
5
95
0
2
Order By: Relevance
“…Studies have reported that use of mHealth as a research tool decreases the potential for recall bias in retrospectively collected data at study visits [2729]; is a cost-effective method to increase adherence to study protocol instructions when compared to one time in person verbal and written instructions to participants [30]; and is useful in contacting difficult to reach study participants [31]. …”
Section: Mhealthmentioning
confidence: 99%
“…Studies have reported that use of mHealth as a research tool decreases the potential for recall bias in retrospectively collected data at study visits [2729]; is a cost-effective method to increase adherence to study protocol instructions when compared to one time in person verbal and written instructions to participants [30]; and is useful in contacting difficult to reach study participants [31]. …”
Section: Mhealthmentioning
confidence: 99%
“…The interventions are described in Multimedia Appendices 6 and 7. Interventions using mobile communication technologies in both developed countries (US [132-154], Norway [155], Ireland [156,157], the Netherlands [158,159], Austria [160], New Zealand [161,162], Australia [163-165], and South Korea [166,167]), and developing ones (Kenya [168], Croatia [169], Singapore [170], Brazil [171], China [172-174], India [175-177], Malaysia [178,179]) have investigated the use of mobile phone-based apps, mobile phone voice call, SMS, and PDAs.…”
Section: Resultsmentioning
confidence: 99%
“…Con objeto de promocionar las conductas saludables de fotoprotección, las campañas han tenido lugar en diferentes ámbitos, incluyendo escuelas, lugares de trabajo, piscinas y recientemente se han llevado a cabo incluso a través de mensajes a móviles para mejorar la adherencia al uso de cremas fotoprotectoras 96 .…”
Section: Discusión -Objetivo Principalunclassified